THE MOTIVATIONS OF FISH FARMER TO BUSINESS CULTIVATION PATIN FISH (Pangasius sutchi) WITH REVENUE SHARING SYSTEM IN VILLAGE OF KUOK SUBDISTRICT OF KUOK KAMPAR REGENCY RIAU PROVINCE. - Putra, Nurdiansyah; ', Kusai; ', Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted on July 10 to 30 2015 in the Village of Kuok Subdistrict of kuok Kampar Regency Riau Province. The research was aimed to know characteristics, the level of motivation and the things that cause Fish Farmer doing the revenue sharing system in fish cultivation. This research used the survey method, that come down to the observation and data collection. It was the research that characteristicts of Fish Farmer in different Villages of Kuok, this matter seen by level of education, business experience Fish Farmer and amount of dependents. That level of motivation Fish Farmer in doing cultivation is generally high, this matter seen by 25 responden with many as 20 lives indicator views, 19 expectations and 19 convictions. While the reason for application of the revenue sharing system in general is to get capital aid (feed, seed and land marketing easy and not at risk). Keywords :Motivation, Fish Farmer, Cultivation Sharing Revenue